VO#054 Quotation for additional pipe works in deep tube well and planter boxes rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the quotation for additional pipe works in deep tube well and planter boxes of BRACU new campus project.